THE CERTAINTY FACTOR METHOD IN DISEASES OF THE SPINAL NERVES - Liana Yuza, Iftitah; Sihombing, Marto; Syahputra, Siswan (Journal of Mathematics and Technology (MATECH), 2023)
The spinal cord is a canal of the brain that runs from the neck to the coccyx. This nerve plays an important role in the process of sending signals from the brain to the rest of the body and vice versa. If this nerve is damaged, there will be interference with some body functions, such as the loss of the ability to move or feel things. Spinal cord patients should be treated immediately by a specialist doctor who deals with problems in neurological diseases. If treatment is not done immediately, the patient may need a longer recovery period. In addition, the possibility of worsening the condition or the appearance of complications will also be greater and some patients who experience diseases of the spinal nerves must undergo treatment or consultation with a doctor to follow up on the causes and symptoms they feel continuously. From the above problems, the authors want to create an application that can help patients to obtain information and make a temporary diagnosis through the application to be built. This application is useful to know the disease of the spinal cord in patients. From the research that has been done, the results of CF calculation with the highest value of 0.9857 or 98.57%, the system identifies that the patient is suffering from ischalgia.